Is a Flat Tax politically feasible in a grown-up Welfare State? - Thilo Schaefer; Andreas Peichl; Clemens Fuest (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2007)
The introduction of a flat tax is supposed to have several advantages. Administration and compliance costs are reduced, as well as incentives for tax evasion. Furthermore, positive employment and growth effects are expected. Despite these advantages, a flat rate tax is not very popular in most Western European countries. The most important objection against a flat tax states that a flat rate tax would be inequitable and unfair. The present paper uses a simulation model based on a unique database of German micro data to provide empirical evidence for the analysis of the equity and efficiency effects as indicators for the political feasibility of flat rate tax reforms. Our analysis shows that the selection of the schedule and tax base parameters are crucial for the effects of flat tax reforms in terms of equity and efficiency. A flat rate tax with a higher basic allowance and a higher single rate has less harmful distributional effects than a flat rate tax with low basic allowance and tax rate. Nevertheless, the scenario with the lowest parameter values for basic allowance and tax rate is the only alternative that leads to positive labour supply and significantly positive welfare effects. Both labour supply and static welfare effects, however, are quite small. Although we have derived our results for the case of Germany, we do think that similar patterns would be observed in other countries of Western Europe. If this proves to be correct, it will be hard for flat tax reforms to invade the grown-up welfare states of "Old Europe".
Keywords: D31; H20; D60; 330; Flat Tax reform; equity; efficiency; distribution; welfare; Flat Tax; Steuerwirkung; Steuerinzidenz; Wohlfahrtseffekt; Soziale Gerechtigkeit; Theorie; Deutschland